Guns, germs, and Steel : A Short History of Everybody for the last 13,000 Years - Diamond, Jared (London Vintage Books, 2005)
This book answers the most obvious, the most important, yet the most difficult question about human history: why history unfolded so differently on different continents. Geography and biography, not race, moulded the contrasting fates of Europeans, Asians, Native Americans, sub-Saharan Africans, and aboriginal Australians. An ambitious synthesis of history, biology, ecology and linguistics, Guns, Germs and Steel is one of the most important and humane works of popular science
Include Maps and Index
Keywords: Human beings--Effect of environment on -- Civilization -- Social evolution